Analisis dan Desain Pengembangan Bahan Ajar dan Sumber Belajar PAI - Nasution, Ummi Nadrah; Qomariah, Siti; Halimah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Textbooks and learning resources play a vital role in the educational process. They function as the primary media for delivering materials, concepts, and values to students. The aim of this research is to analyze and design the development of teaching materials and learning resources for Islamic Religious Education (PAI) using a qualitative research method of literature review. This study involves the collection and analysis of relevant literature to identify the strengths and weaknesses of existing PAI teaching materials, and to formulate innovative and effective design strategies. The analysis results indicate that current PAI teaching materials are often less contextual, less interactive, and have not fully utilized digital technology. The implications of this research include the need for policy support and teacher training to implement modern and effective teaching materials, thereby improving the quality of Islamic religious education in schools. This research is expected to serve as a reference for the development of more adaptive and innovative PAI teaching materials.